Repair and regeneration of tracheal surface epithelium and submucosal glands in a mouse model of hypoxic-ischemic injury - HEGAB, AHMED E. (2012)
BACKGROUND AND OBJECTIVE: The heterotopic syngeneic tracheal transplant mouse model is an acute hypoxic-ischemic injury model that undergoes complete repair and regeneration. We hypothesized that the repair and regeneration process of the surface epithelium and submucosal glands would occur in a reproducible pattern that could be followed by the expression of specific markers of epithelial cell types. METHODS: We used the syngeneic heterotopic tracheal transplant model to develop a temporal and spatial map of cellular repair and regeneration by examining the tracheal grafts at post-transplant days 1, 3, 5, 7, 10 and 14. We used pulsed BrdU and immunofluorescent staining to identify and follow proliferating and repairing cell populations. RESULTS: We confirmed the reproducibility of the injury and repair in the model and we found a distinct sequence of reappearance of the various stem/ progenitor and differentiated cell populations of the tracheal surface epithelium and submucosal glands. In the initial phase, the basal and duct cells that survived the injury proliferated to re-epithelialize the basement membrane with K5 and K14 expressing cells. Then these cells proliferated further and differentiated to restore the function of the epithelium. During this repair process, TROP-2 marked all repairing submucosal gland tubules and ducts. Non-CCSP-expressing serous cells were found to differentiate 4–5 days before Clara, mucus and ciliated cells. CONCLUSIONS: Improving our understanding of the reparative process of the airway epithelium will allow us to identify cell-specific mechanisms of repair that could be used as novel therapeutic approaches for abnormal repair leading to airway diseases.